Single nucleotide editing without DNA cleavage using CRISPR/Cas9‐deaminase in the sea urchin embryo. Issue 12 (13th October 2017) - Shevidi, Saba; Uchida, Alicia; Schudrowitz, Natalie; Wessel, Gary M.; Yajima, Mamiko
Abstract : Background: A single base pair mutation in the genome can result in many congenital disorders in humans. The recent gene editing approach using CRISPR/Cas9 has rapidly become a powerful tool to replicate or repair such mutations in the genome. These approaches rely on cleaving DNA, while presenting unexpected risks.Results: In this study, we demonstrate a modified CRISPR/Cas9 system fused to cytosine deaminase (Cas9‐DA), which induces a single nucleotide conversion in the genome. Cas9‐DA was introduced into sea urchin eggs with sgRNAs targeted for SpAlx1, SpDsh, or SpPks, each of which is critical for skeletogenesis, embryonic axis formation, or pigment formation, respectively. We found that both Cas9 and Cas9‐DA edit the genome, and cause predicted phenotypic changes at a similar efficiency. Cas9, however, resulted in significant deletions in the genome centered on the gRNA target sequence, whereas Cas9‐DA resulted in single or double nucleotide editing of C to T conversions within the gRNA target sequence.Conclusions: These results suggest that the Cas9‐DA approach may be useful for manipulating gene activity with decreased risks of genomic aberrations. Developmental Dynamics 246:1036–1046, 2017 . © 2017 Wiley Periodicals, Inc. Key Findings: Cas9‐Deaminase modifies single nucleotides by conversion without dsDNA cleavage. Cas9‐Deaminase most effectively converts cytosine to thymine between 7‐20 bases upstream of the PAM sequences of the targeted sgRNA site. CRISPR/Cas9‐Deaminase edits the genome at a similar rate to standard CRISPR/Cas9 systems. Gene modification by Cas9‐Deaminase was demonstrated by targeting Alx1, Dishevelled, and polyketide synthetase (Pks).